Simbol dan Identitas: Kajian Tentang Negosiasi dan Konsolidasi Terhadap Simbol Budaya Dalam mempertahankan Identitas Masyarakat Riau - Noor Efni Salam (KOM & REALITAS SOSIAL, 2012)
This research is aimed at analyzing the process of negotiation and consolidation on the symbol of clothing and architecture of Riau Malay, and different perceptions in its intepretation. This is done as an effort to unify the meaning of these symbols as cultural identity of the people of Riau. This is a qualitative research with Riau people as informants which purposively selected. The results showed that the clothing symbols negotiated and consolidate, while architecture symbol still in the process of consolidative.